Synergetic Control-Based Sea Lion Optimization Approach for Position Tracking Control of Ball and Beam System - Al-Khazraji, Huthaifa; Albadri, Kareem; Almajeez, Rawaa; Humaidi, Amjad J (International Journal of Robotics and Control Systems, 2024)
One of the most difficult systems to control is the ball and beam (BnB) system due to its under-actuation, instability, and nonlinearity. To address these challenges, this paper presents an application of using the nonlinear synergetic control (SC) algorithm for position tracking control of the BnB system. A swarm optimization method based on sea lion optimization (SLO) has also been used to achieve an optimum dynamic performance by adjusting the suggested controller’s parameter. The Integral Time of Absolute Errors (ITAE) is employed by the SLO as an objective function to adjust the design parameters of the suggested SC. Using MATLAB software, a comparison has been made between the SC controller and the classical state feedback controller (SFC) to test the effectiveness of the suggested control algorithm. The findings illustrate that the suggested SC offers better transient response in terms of reducing the settling time and the overshoot than SFC. The effect of the external disturbance has also been examined. It has been found that SC provides more robustness performance than SFC.